Conceptualizations of well-being in adults with visual impairment: A scoping review - Heinze, Nikki; Davies, Ffion; Jones, Lee; Castle, Claire L.; Gomes, Renata S. M. (Frontiers in Psychology, 2022)
Background: Despite its ubiquity, it is often not clear what organisations and services mean by well-being. Visual impairment (VI) has been associated with poorer well-being and well-being has become a key outcome for support and services for adults living with VI. A shared understanding of what well-being means is therefore essential to enable assessment of well-being and cross-service provision of well-being support. Objectives: To provide an overview of the ways in which well-being has been conceptualised in research relating to adults living with VI. Eligibility criteria: Articles were included in the review if the article discussed well-being in the context of adults living with VI, was available in English and as a full text. Data sources: A systematic search using search terms relating to VI and well-being was conducted in EBSCOHost (Medline, CINHL) and Ovid (Embase Classic, Embase, Emcare 1995, Health + Psychosocial, HMIC Health Management Info, APA, PsycArticles, PsycInfo, PsycTests). Charting: A team of three reviewers screened titles, abstracts and full-texts articles and extracted data. Ambiguous articles were referred to the research group and discussed. Results: Of 10,638 articles identified in the search, 249 were included in the review. These referred to 38 types of well-being. The most common types were general well-being (n=99;39.8%) emotional well-being (n=85, 34.1%) and psychological well-being (n=65, 26.1%). Most articles (n=150;60.2%) referred to one type only, with a maximum of 9 listed in one article. A large number of articles did not clearly define well-being. A wide range of indicators of well-being related to the domains of hedonia, mood, positive and negative affect, quality of life, mental health, eudaimonia, self/identity, health, psychological reactions to disability and health problems, functioning, social functioning and environment, were extracted, many of which were used just once. Conclusions: There remains a lack of consensus on how well-being is conceptualised and assessed in the context of adult VI. A standardised multi-domain approach derived with input from adults with VI and practitioners working with them is required to enable comparison of findings and cross-organisational provision of support.